2019
DOI: 10.1080/15548627.2019.1659573
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Spt4-Spt5 complex regulates the expression of ATG8 and ATG41

Abstract: Macroautophagy/autophagy, a highly conserved dynamic process, is one of the major degradative pathways in cells. So far, over 40 autophagy-related (ATG) genes have been identified in Saccharomyces cerevisiae, most of which have homologs in more complex eukaryotes. Autophagy plays a crucial role in cell survival and maintenance, and its dysfunction is related to various diseases, indicating that the proper regulation of autophagy is important. Although the overall process of autophagy has been extensively studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…However, other studies showing a role of Spt5 in early transcription proved that neither the Spt5 CTR (C’-terminal repeats) domain, which can be phosphorylated, nor the Spt4 partner are important for promoter escape ( 65 ). Interestingly, Spt4 was shown to play a role in autophagy as an inhibitor of Spt5 phosphorylation ( 16 ) and it is possible that it is also necessary for the progression of meiosis. This putative role of Spt4 is especially interesting because of the evidence indicating that dephosphorylation of Spt5 decreases the elongation rate of the RNA Pol II complex ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other studies showing a role of Spt5 in early transcription proved that neither the Spt5 CTR (C’-terminal repeats) domain, which can be phosphorylated, nor the Spt4 partner are important for promoter escape ( 65 ). Interestingly, Spt4 was shown to play a role in autophagy as an inhibitor of Spt5 phosphorylation ( 16 ) and it is possible that it is also necessary for the progression of meiosis. This putative role of Spt4 is especially interesting because of the evidence indicating that dephosphorylation of Spt5 decreases the elongation rate of the RNA Pol II complex ( 66 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Spt5 is involved in RNA maturation, whereas Spt4 is involved in chromosome transmission and the assembly of centromere heterochromatin ( 12–15 ). Furthermore Spt4 functions as a negative regulator of autophagy through inhibition of Spt5 phosphorylation, suggesting that their roles do not necessarily overlap ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sample Preparation and Mass Spectrometry. Purified ATG9 was directly digested on beads overnight according to the filter-aided sample preparation (FASP) protocol, and the analysis was carried out essentially as described previously (49).…”
Section: Two-mentioning
confidence: 99%
“…Upon deletion of SPT4, Wen et al found an increase in both mRNA and protein levels of ATG8/Atg8 and ATG41/Atg41 in nutrient-rich conditions. Moreover, cells lacking Spt4 display increased autophagy activity, suggesting Spt4 negatively regulates autophagy [7].…”
mentioning
confidence: 99%